ผลของโปรแกรมการบำบัดทางความคิดและพฤติกรรมที่ใช้การสนับสนุนทางอินเทอร์เน็ตต่อภาวะซึมเศร้าในผู้เสพติดสุรา - รุ่งอรุณ โทวันนัง (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This study is a quasi-experimental pretest-posttest control group desing. The objectives were to compare: 1) depression of males with alcohol dependence before and after received the internet-supported cognitive behavior therapy program, and 2) depression of males with alcohol dependence who received internet-supported cognitive behavior therapy program and those who received regular nursing care. The sample consisted of 40 male alcohol dependence with depression, who met the inclusion criteria, and were receiving treatment in outpatient unit, Thanyarak Khonkaen hospital. They were matched-pairs by depression score and randomly assigned to the experimental and control group, 20 subjects in each group. The experimental group received the internet-supported cognitive behavior therapy program developed by the researcher, whereas the control group received regular caring activities. Research instruments comprised of: 1) the Internet-supported cognitive behavior therapy program, 2) Beck Depression Inventory, 3) the Automatic Though Questionnare, and 4) the Personal information questionnaire. The 2nd and 3rd instrument had Cronbach’s Alpha Coefficient reliability of .81 and .89, respectively. Descriptive statistics and t-test were used in data analysis. The findings of this research are as follows: 1. depression of males with alcohol dependence who received the internet-supported cognitive behavior therapy program was significantly lower than that before (p < .05 ). 2. depression of males with alcohol dependence who received the internet-supported cognitive behavior therapy program was significantly lower than those who received the regular nursing care ( p < .05 ).